2018
DOI: 10.21608/aeji.2018.13297
|View full text |Cite
|
Sign up to set email alerts
|

Serological and Immunohistochemical Detection of Helicopacter pylori Infection among Egyptian Hepatitis C Virus Patients

Abstract: Background and study aim: Helicobacter pylori infection is distributed worldwide. H. pylori colonize the liver and increase the severity of the liver pathogenesis. The aim of the present study was to detect the H. pylori in the HCV patients using serology and immunohistochemistry diagnostic methods. The aim was extended to evaluate the hematological and biochemical changes during the co-infection. Materials and Methods: ELISA and immunohistochemistry diagnostic methods were utilized to examine patients chronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 36 publications
0
1
1
Order By: Relevance
“…In our study, H. pylori infection recorded prevalence among HCV patients with thrombocytopenia 65%( 65/100) versus 35% (35/100) H. pylori negative this agreement with Takashima et al (2016) 1 The research included sixty-five patients with HCVrelated CLD and thrombocytopenia, of which 30 (46%) were H. pylori-positive. in contrast to Ibrahim et al, (2018) 9 Using ELISA and IHC, respectively, the average incidence of H. pylori was 10.81 % and 8.00 %. Aljarad S et al, (2018) 10 and Lee et al, (2020) 11 reported the frequency of Helicobacter pylori infection was 72% and 54.3% respectively in ITP patients in contrast to Sultan et al, (2016) 12 show frequency of Helicobacter pylori infection in ITP 11.1%.…”
Section: H Pyloricontrasting
confidence: 60%
“…In our study, H. pylori infection recorded prevalence among HCV patients with thrombocytopenia 65%( 65/100) versus 35% (35/100) H. pylori negative this agreement with Takashima et al (2016) 1 The research included sixty-five patients with HCVrelated CLD and thrombocytopenia, of which 30 (46%) were H. pylori-positive. in contrast to Ibrahim et al, (2018) 9 Using ELISA and IHC, respectively, the average incidence of H. pylori was 10.81 % and 8.00 %. Aljarad S et al, (2018) 10 and Lee et al, (2020) 11 reported the frequency of Helicobacter pylori infection was 72% and 54.3% respectively in ITP patients in contrast to Sultan et al, (2016) 12 show frequency of Helicobacter pylori infection in ITP 11.1%.…”
Section: H Pyloricontrasting
confidence: 60%
“…Agreement between ELISA and immunohistochemistry was calculated according to Ibrahim et al [34][35][36][37].…”
Section: Assays Agreement Percentage Calculationmentioning
confidence: 99%